(108)^(1/2) - 27^(1/2)
= (36*3)^(1/2) - (9^3)^(1/2)
= ((36)^(1/2)3^(1/2)- 9^(1/2)3^(1/2)
= 6*3^(1/2) - 3*3^(1/2)
= 3^(1/2)(6-3)= 3*3^(1/2)
the steps are find prodiuct of a perfect square and another then take square root.
2006-10-04 06:04:57
·
answer #1
·
answered by Mein Hoon Na 7
·
0⤊
0⤋
I believe to calculate the square root you can also use the exponent 1/2.
In other words: instead of finding the square root of X
Raise X to the power of 1/2. That is: X ^ (1/2)
2006-10-04 06:06:52
·
answer #2
·
answered by pinduck85 4
·
0⤊
0⤋
108=9x4x3
27=9x3
therfore root 108= 3x2xroot 3= 6 root3
root 27= 3root 3
so 6 root3 - 3 root 3 = 3 root 3
2006-10-04 06:08:32
·
answer #3
·
answered by arsan600 1
·
0⤊
0⤋
well its pretty easy. Find the square root of 108 and the square root of 27 and then subtract the two. Hope that helps
2006-10-04 05:59:17
·
answer #4
·
answered by Taylor R 3
·
0⤊
1⤋
find the square root of 108 and take away the square root of 27 by findin them on a calculator, DONT FIND THE SQUARE ROOT OF 81.
2006-10-04 06:02:13
·
answer #5
·
answered by Stuart H 1
·
0⤊
0⤋
√ is done by holding down the ALT key and typing 251.
Your answer is: 5.19615242269 approximately.
√108= 6√3
√27=3√3
so 6√3-3√3=3√3 or 5.19615242269 (approximately)
2006-10-04 07:25:40
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
Factor out perfect squares from the radicand, and then simplify. Your answer will idealy be in terms of the square root of a much simpler radicand.
2006-10-04 05:59:40
·
answer #7
·
answered by aristotle2600 3
·
0⤊
0⤋
√108 - √27
- - - - - - - - - - - - - - - - - - - - - - - - - - - - - -
Solving For √108
√108 = √4 √27
√108 = 2 √9 √3
√108 = 2 x 3 √3
√108 = 6 √3
- - - - - - - - - - - - - - - - - - - - - - - - - - - - -
solving for √27
√27 = √9 √3
√27 = 3 √3
- - - - - - - - - - - - - - - - - - - - - - - - - - - - -
√108 - √27
6 √3 - 3 √3
3 √3
The answer is 3√3
The solution set is { 3√3 }
2006-10-04 07:33:17
·
answer #8
·
answered by SAMUEL D 7
·
0⤊
0⤋
you may want to simplify sq. root 20 into 2 sq. root of 5 and sq. root of 8 into 2 sq. root of two accordingly, you may want to component out 2, which leaves 2(sq. root of 5 + sq. root of two)^2 by skill of simplifying further, 2(5+2square root of 5 * sq. root of two + 2) 2(7+ 2 sq. root of 10) accordingly the finest answer will be: 14+ 4square root of 10
2016-11-26 02:30:32
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
sqrt 108 - sqrt 27
= ( sqrt 9 times sqrt 4 times sqrt 3 ) - (sqrt 9 times sqrt 3 )
= ( 3 times 2 times sqrt 3 ) - ( 3 times sqrt 3 )
= ( 6 times sqrt 3) - (3 times sqrt 3 )
= 3 times sqrt 3
= 3 times 1.732 = 5.196..
2006-10-04 07:10:27
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋